Profil EKG Pasien Hipertensi di Poliklinik Jantung - Fira Soraya; Elyana Asnar; Muhammad Aminuddin (Jurnal Ners, 2016)
Introduction: It covers 31.7% of people with hypertension in Indonesia. Hypertension can cause changes in the anatomy and/or function of the heart, that may cause morbidity and/or mortality. The changes itselves can be diagnosed with electrocardiography (ECG). Based on that background, the objective of this study is to recognize the ECG profile of hypertension patients in Cardiology Outpatient Clinic RSUD Dr. Soetomo Surabaya.Methods: The design of this study was observational descriptive study. The samples were obtained through primary and secondary data from patients’ medical history within the period of 1st until 31st March. The collected data was managed based on gender, age and the present of left ventricular hypertrophy.Results: There were 140 hypertension patients throughout this study period. The prevalence of hypertension was the same between men and women. The highest prevalency of hypertension was in age 51 to 60. Two ECG results showed left ventricular hypertrophy and 138 ECG results showed other than left ventricular hypertrophy, such as arrhythmia and atrial fibrillation.Conclusion: The results show that there is no different between men and women, where other previous researches show that the result is different between men and women. This can be caused by many factors.